The correlation between genomic DNA total methylation and codon 12 K-ras gene point mutations in primary endometrial cancers - Semczuk, Andrzej; Keith, Gérard; A. Jakowicki, Jerzy; Postawski, Krzysztof; Miturski, Roman; Baranowski, Włodzimierz (Menopause Review/Przegląd Menopauzalny, 2002)
Materials and methods: We analyzed the methyldeoxycytosine (m 5 dC) and the deoxycytosine content of genomic DNAs isolated from 44 primary endometrial cancers and 25 normal endometrium samples using enzymatic digestion into nucleotides, 32 P postlabelling, two-dimensional thin-layer chromatography on cellulose plates and bioimaging. Results: The overall m 5 dC of the uterine cancer DNAs (3.43%±0.47%) was significantly higher than that of the normal proliferative endometrium (2.94%±0.4%, p=0.003) and lower than that of the secretory endometrium DNAs (3.75%±0.47%, p=0.03). In addition, RFLP-PCR revealed K-ras gene point mutations in 25% (11 cases) of the cancers. The m 5 dC of neoplasms with mutant K-ras was lower than that of cancers bearing the wild-type gene (3.19%±0.31% vs. 3.51%±0.48%, p=0.047). Among all endometrial cancer DNAs six were found to be hypomethylated, eight were hypermethylated, whereas the remaining 30 had m 5 dC within range of normal endometrium. Lower level of DNA methylation seemed to be associated with diminished tumor invasiveness. K-ras gene alterations were absent in all hypermethylated cancer DNAs. Conclusions: Our results suggest that alterations in overall DNA methylation seem to be a result of neoplastic transformation and could therefore be used as a prognostic molecular marker of endometrial cancer. DNA hypomethylation may facilitate the mutability of the K-ras gene.